1985
DOI: 10.1007/bf01012115
|View full text |Cite
|
Sign up to set email alerts
|

Role of plant volatiles in resistance of selected rice varieties to brown planthopper,Nilaparvata lugens (St�l) (Homoptera: Delphacidae)

Abstract: Rice plant volatiles extracted as steam distillates significantly affected the behavior and biology of the brown planthopper,Nilaparvata lugens (Stål). In a multichoice test, more females settled and fed on tillers of a susceptible rice variety "Taichung Native 1" (TN1), sprayed with its own extract or acetone than on TN1 tillers sprayed with the extract of the resistant variety "ARC6650" or "Ptb33." In another test,N. lugens females ingested significantly more of a 10% sucrose solution mixed with TN1 steam di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…The rice variety Ptb33 showed a higher degree and a broader spectrum of BPH resistance than has been described previously24293358. E.R.…”
Section: Discussionmentioning
confidence: 60%
“…The rice variety Ptb33 showed a higher degree and a broader spectrum of BPH resistance than has been described previously24293358. E.R.…”
Section: Discussionmentioning
confidence: 60%
“…The candidate gene should be further confirmed A previous study reported that BPH resistance in rice cultivars carrying Bph3 exhibited antixenosis (Saxena and Okech 1985). This means, BPH had a tendency to move away from resistant plants after some time.…”
Section: Bph Resistance In Rht Is Associated With a Series Of Genesmentioning
confidence: 94%
“…BEHAVIORAL STUDIES INDICATE that chemoreception plays a part in host plant selection and acceptance and in the control of feeding in the rice brown plant hopper, Nilaparvata lugens (Stål) (Obata et al 1983, Saxena andOkech 1985). The Þne structure of putative chemoreceptors on the antennae (Aljunid and Anderson 1983) and proboscis (Foster et al 1983a(Foster et al , 1983b has been described together with the external features of sensilla on the tarsi (Lö sel and Goodman 1987).…”
mentioning
confidence: 97%